PERAN PROGRAM KONSELING BERBASIS NILAI AGAMA DALAM MEMBENTUK WAWASAN YANG TOLERAN DAN MODERAT PADA SISWA SEKOLAH DASAR - Moh Saiful Bahri; Siti Mumun Muniroh (CV. ADIBA AISHA AMIRA, 2023)
This research aims to develop a counseling program based on religious values to form a tolerant and moderate outlook. This type of research is qualitative through literature study and field study including observation, documentation and interviews. In this era of rapid development, it is important for individuals to have a tolerant and moderate outlook, especially in the context of social development and interfaith relations. Therefore, developing a counseling program based on religious values is very relevant. In this research, the author conducted a review of literature related to the development of a counseling program based on religious values and its impact in forming a tolerant and moderate outlook. Some of the subjects discussed in this literature review include understanding religion, relevant religious values, counseling skills, and effective pedagogical approaches. The results of this literature review show that the development of a counseling program based on religious values can be effective in forming a tolerant and moderate outlook (Rahman, 2023). This program can help individuals understand and internalize positive religious values, thereby influencing their attitudes and behavior in accepting differences and maintaining harmony between religious communities. Developing a counseling program based on religious values can be effective in forming a tolerant and moderate outlook. This program provides benefits to individuals in understanding and internalizing positive religious values. This also influences their attitudes and behavior in accepting differences and maintaining harmony between religious communities. In order to develop an effective religious values-based counseling program, the author recommends the need for training for counselors to understand and apply pedagogical approaches that are appropriate to the religious and cultural context of society (Mubarok & Muslihah, 2022). Apart from that, further research is also needed to evaluate the effectiveness of this program and determine indicators of its success in forming a tolerant and moderate outlook. Thus, this research has important implications in supporting harmonious social development and respecting differences in a multicultural society. A counseling program based on religious values can be an effective means of forming a tolerant and moderate outlook, thereby making a positive contribution to the development of individuals and society as a whole.